Evaluation of length of central venous catheter inserted via cubital route in Indian patients - Joshi, Saurabh (Medknow Publications, 2010)
AIM: Peripherally inserted central venous catheters (PICCs) are popular due to the ease of insertion, low cost and low risk of complications. Anteroposterior (AP) chest radiograph (CXR) is then obtained to assess the location of the catheter tip. But poor-quality X-rays remain a significant problem. We planned a study using radiopaque marker at sternal angle, as a radiological landmark, to relate height of the patient and optimal length of PICC fixation, at the antecubital fossa, and to know the incidence of malpositioning. MATERIALS AND METHODS: A total of 200 patients aged above 20 years, scheduled for elective major cancer surgeries were studied. Vygoflex PUR, 16-G catheter, length 70 cm was used. The right or the left arm was chosen depending on the availability of veins. Catheter tip was observed in the post procedure CXR. RESULTS: 200 patients [100 patients in group 1 (length of catheter fixation at antecubital fossa 45 cm) and 100 patients in group 2 (length of catheter fixation 50 cm)] were enrolled. The groups were further subdivided into 1a, 1b, 2a, 2b and results tabulated. CONCLUSIONS: Appropriate length of catheter fixation for group 1a was <45 cm, group 1b = 45 cm, group 2a = 50 cm, and for group 2b it was ≥50 cm. Gender and arm (right or left) did not have any bearing on the length of fixation. Incidence of malpositioning (15.5%) was more in right-sided catheters, more so, in short heighted people. PICC insertion via cubital route stands better compared with other routes, viz., Internal jugular vein IJV, subclavian and femoral.